Does leaf gas exchange correlate with petiole xylem structural traits in Ulmus laevis seedlings under well-watered and drought stress conditions?. (22nd July 2022) - Gebauer, Roman; Urban, Josef; Volařík, Daniel; Matoušková, Marie; Vitásek, Roman; Houšková, Kateřina; Hurt, Václav; Pantová, Petra; Polívková, Terezie; Plichta, Roman
Abstract: Several studies have shown that petiole xylem structure could be an important predictor of leaf gas exchange capacity, but the question of how petiole xylem structure relates to leaf gas exchange under different environment conditions remains unresolved. Moreover, knowledge of the amount of leaf gas exchange and structural variation that exists within a single species is also limited. In this study, we investigated the intraspecies coordination of leaf gas exchange and petiole xylem traits in 2-year-old seedlings of Ulmus laevis Pall. under well-watered and drought conditions. It was found that all studied petiole xylem traits of the elm seedlings were positively correlated with each other. This shows that the development of petiole xylem structure is internally well-coordinated. Nevertheless, the lower correlation coefficients between some petiole xylem traits indicate that the coordination is also individually driven. Drought stress reduced all studied leaf gas exchange traits and significantly increased intraspecies variation. In addition, drought stress also shifted the relationships between physiological traits and exhibited more structure–function relationships. This indicates the importance of petiole xylem structure in dictating water loss during drought stress and could partly explain the inconsistencies between leaf structure–function relationships studied under optimal conditions. Although several structure–function traits were related, the wide ranges of correlation coefficients indicate that the internal coordination of these traits substantially differs between individual elm seedlings. These findings are very important in the context of expected climatic change, as some degree of intraspecies variation in structure–function relationships could ensure the survival of some individuals under different environmental conditions.